PERAN PENDIDIKAN AGAMA KRISTEN DALAM MENANGGULANGI PERGAULAN BEBAS PESERTA DIDIK DI ERA DIGITAL - Defilia Osin Pakulla; Nelince Inseren Mofu, Minggu Tappi', Daniel Matalangi, Selki Harsel (ADISAM PUBLISHER, 2025)
Free association is a serious challenge in the moral development of students, especially in the digital era that accelerates the spread of negative values. Christian Religious Education (PAK) has a strategic role in shaping the character of students so that they have strong faith and are able to reject bad influences from the surrounding environment. This article discusses the nature of free association, the role of PAK in shaping character, and strategies that can be applied in learning to fortify students from deviant associations. In addition, collaboration between schools, churches, and families is presented as an important element in creating an environment that is conducive to the moral and spiritual development of students. With strong synergy between the three institutions, students can grow into individuals who are not only intellectually intelligent, but also adhere to Christian values in their daily lives